Long-chain alkanes and fatty acids from Ludwigia octovalvis weed leaf surface waxes as short-range attractant and ovipositional stimulant to Altica cyanea (Weber) (Coleoptera: Chrysomelidae). Issue 3 (30th January 2017) - Mitra, S.; Sarkar, N.; Barik, A.
Abstract: The importance of leaf surface wax compounds from the rice-field weed Ludwigia octovalvis (Jacq.) Raven (Onagraceae) was determined in the flea beetle Altica cyanea (Weber) (Coleoptera: Chrysomelidae). Extraction, thin layer chromatography and GC-MS and GC-FID analyses of surface waxes of young, mature and senescent leaves revealed 20, 19 and 19 n -alkanes between n -C15 and n -C35, respectively; whereas 14, 14 and 12 free fatty acids between C12:0 and C22:0 fatty acids were identified in young, mature and senescent leaves, respectively. Tricosane was predominant n -alkane in young and mature leaves, whilst eicosane predominated in senescent leaves. Heneicosanoic acid, palmitic acid and docosanoic acid were the most abundant free fatty acids in young, mature and senescent leaves, respectively. A. cyanea females showed attraction to 0.25 mature leaf equivalent surface waxes compared with young or senescent leaves in a short glass Y-tube olfactometer bioassay. The insects were attracted to a synthetic blend of 0.90, 1.86, 1.83, 1.95, 0.50 and 0.18 µg ml −1 petroleum ether of hexadecane, octadecane, eicosane, tricosane, palmitic acid and alpha-linolenic acid, respectively, comparable with the proportions as present in 0.25 mature leaf equivalent surface waxes. A. cyanea also laid eggs on a filter paper moistened with 0.25 mature leaf equivalent surface waxes or a synthetic blend of 0.90, 1.86, 1.83, 1.95, 0.50 and 0.18 µg ml −1 petroleum ether of hexadecane, octadecane, eicosane, tricosane, palmitic acid and alpha-linolenic acid, respectively. This finding could provide a basis for monitoring of the potential biocontrol agent in the field.